Cover Feature: Photocatalytic CO2 Reduction under Continuous Flow High‐Purity Conditions: Influence of Light Intensity and H2O Concentration (ChemCatChem 23/2017). Issue 23 (8th December 2017) - Dilla, Martin; Mateblowski, Alina; Ristig, Simon; Strunk, Jennifer
Abstract : The Cover Feature shows the reaction parameters that influence the yield of methane in the photocatalytic reduction of carbon dioxide on bare TiO2 under continuous‐flow reaction conditions. In their Full Paper, M. Dilla et al. provide evidence that the reaction is truly photon‐driven, with UV light illumination as predominant prerequisite for product formation. Owing to a dominating influence of charge carrier recombination, the yields increase only with the square root of light intensity. Slightly elevated temperatures can increase methane yields, but high amounts of water are detrimental. In contrast, the reaction can proceed with even small amounts of physisorbed water. More information can be found in the Full Paper by M. Dilla et al. onpage 4345 in Issue 23, 2017 (DOI:10.1002/cctc.201701189 ).